COMPARITIVE ACCOUNT OF ENZYME Β FRUCTOFURANOSIDASE ACTIVITY & PROTEIN CONTENT IN DIFFERENT RACES OF 5TH INSTAR LARVAE OF BOMBYX MORI L. - MAMATHA C; BELA ZUTSHI; JAYAPRAKASH (International Journal of Pharma and Bio Sciences, 2016)
The silkworm Bombyx mori L is known for the production of therapeutic bioactive enzymes. Studies were conducted to analyse the total protein content and enzyme activity of β- fructofuranosidase from the midgut region of five different races namely PM, NK2, CSR2, MH1 and RP9×NK2. Protein content was determined by Lowry’s method and enzyme activity was determined by DNS method. On analysis, the protein content and enzyme activity was found to be highest in RP9×NK2 and lowest in PM, in comparison to other races.